Evaluating 6PPD-Q bioavailability and biotransformation in zebrafish by diffusive gradients in thin-films - Ren, Suyu; Xia, Yuxiang; Wang, Mengfei; Zhao, Sijia; Wu, Xiao; Man, Mingsan; Du, Yize; Yang, Qixia; Lv, Min; Chen, Lingxin; Ding, Jing (Academic Press, 2026)
The bioavailability assessment of highly environmentally concerned substance 6PPD-Q for aquatic organisms is of great significance for studying its bioaccumulation potential and environmental risks. Traditional bioanalytical methods face limitations in efficiency and field applicability. This study represented the first to evaluate the novel application of diffusive gradients in thin-films (DGT) technology for predicting the bioavailability of 6PPD-Q in zebrafish (Danio rerio) by simultaneously exposing zebrafish and DGT devices to solutions containing different 6PPD-Q concentrations (5−100 μg L−1). Results showed that DGT could accurately determine the time-weighted averaged (TWA) concentration of 6PPD-Q despite the strong concentration fluctuations caused by degradation and biological uptake. Although the in vivo bioaccumulation and biotransformation of 6PPD-Q in zebrafish are likely complex, a strong positive correlation (R2 = 0.786−0.996, p < 0.05) between DGT enrichment and zebrafish accumulation was observed at environmentally relevant concentrations (1.90−20.8 μg L−1), confirming DGT's reliability in predicting 6PPD-Q bioavailability. Through high-resolution liquid chromatography-mass spectrometry, four metabolites (hydroxylated, dihydroxylated, sulfated, and glucuronidated derivatives) of 6PPD-Q were identified to be produced by zebrafish, and were revealed to be continuously and rapidly excreted into the solution. Notably, DGT effectively captured trace-level metabolite dynamics, yielding superior detection sensitivity and clearer kinetic profiles than direct biological sampling. This study pioneers the application of DGT for assessing the bioavailability of hydrophobic organic pollutants and their metabolites, demonstrating that DGT is a valuable tool for assessing the bioavailability of 6PPD-Q in aquatic organisms and for characterizing the in-situ release kinetics of its metabolites, providing novel insights into 6PPD-Q's environmental behavior.